ANALYSIS OF FACTORS AFFECTING INTENTION TO USE E-WALLETS DURING THE COVID-19 PANDEMIC - Setiani Putri Hendratno (Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2022)
Nowadays, the COVID-19 pandemic has greatly impacted human lives all around the world. One of the impacts that is quite noticeable is changes in lifestyle that must be adapted to the health protocols to reduce the spread of COVID-19. Along with the COVID-19 Pandemic, Indonesia also facing th era of e-payment, especially e-Wallet. E-Wallet is one of e-Payment which is server-based on the form of application that is used to store the user’s information. E-wallet can be used for e-commerce transaction and also as one of payment in offline store in Indonesia. They provide quick payment from the customer’s phone and also provide discount as their promotion. This study aims to analyze the influence of factors from the DeLone and McLean ISS Model which is user satisfaction, system quality and service quality, and other factors such as perceived COVID-19 risk, perceived usefulness, perceived risk, trust, economic benefit, government support, security risk, and financial risk towards the intention to use e-Wallets in offline stores during COVID-19. The data of this research were obtained from distributing questionnaires via google form to the e-Wallet users in Indonesia. By using the SEM-PLS method, research data from 300 respondents were analyzed with SmartPLS version 3.2.8 software. The results showed that perceived COVID-19 risk, user satisfaction, and trust influences the intention to use e-Wallet in offline stores during the pandemic. In addition, the user satisfaction is also influenced by system quality and service quality. Meanwhile, the perceived usefulness and perceived risk did not affect the intention to use e-Wallet in offline stores during COVID-19.